Ensino de Filosofia nas variantes do IFAL - Prudente, Thiago Pessoa (2017)
This study deals with the teaching of Philosophy as a subject that is regularly offered in higher degree courses, in the distance modality, existing in one of the Federal Institutions of Higher Education installed in the State of Alagoas. The objective is to gather information and analyze the situation of Philosophy teaching in the face of problems and difficulties involving students, teachers and the reality of higher education and distance in Alagoas, observed in the practice of the higher courses offered in the distance modality by the Federal Institute of Alagoas Through the Open University of Brazil Program. In order to carry out this study, it was decided to structure and develop the ideas and the text in six chapters that range from the historical survey of the central elements of this work, through the exposition of the research methodology used in the process until the analysis of the role and importance of the Philosophy and its teaching in the structure of the current Brazilian education, and, for training teachers to teach philosophy in higher education through distance education. In the chapters the historical survey is carried out, necessary for the foundation, conceptualization and definition of the elements studied in this work and for the understanding and reflection of the current reality that structures the field of action and study of this research. The methodology chosen for the research is emphasized, emphasizing the definition and conceptualization of the terms researched, informing and explaining the research methodology used, of a qualitative nature, of an applied and explanatory nature, whose technical procedures used come from the joint use of the Methods of bibliographic research, documentary research and Content Analysis, in addition to presenting the field of study from the samples / problems of the research, the Federal Institute of Alagoas. We present the discussions and understandings about the teaching of Philosophy in practice, what its role and importance in higher education are, what are the challenges, problems and issues found in the Brazilian reality and especially in Alagoas for the development of Pedagogical practices related to this activity, in addition to discussing the training for the teaching of philosophy in higher education and distance education. It is presented the guidelines and information for the organization and structuring of the undergraduate courses that occur, both in person and in distance mode, throughout Brazil, while presenting the relationship between Philosophy and its teaching With the courses studied. The analysis of the situation, problems and challenges involved in the organization and implementation of the higher courses offered in the distance modality by the Federal Institute of Alagoas, as well as the role and importance of Philosophy and its teaching in the constitution and organization of Curricula of the courses, as in the organization and structuring of the disciplines and virtual learning environments. In the final considerations, a retrospective of this study is presented presenting the results of the research and trying to point out ways, based on the information analyzed, that help in the improvement and development of Philosophy teaching, as a discipline, existing in the higher courses offered at a distance by the Institute Federal of Alagoas.